Depositional Sequences of the Itararé Group in the Region of Mafra (SC) and their Regional Correlation - Kraft, Ronaldo Paulo; Vesely, Fernando Farias; Weinschütz, Luiz Carlos (Anuário do Instituto de Geociências, 2022)
The Itararé Group, Permocarboniferous of the Paraná Basin, has its deposition associated with the Late Paleozoic Ice Age (LPIA), which encompassed multiple glacial advance-retreat cycles. Recognizing the nature of the processes that form these rocks is essential to understand the diversity of glacial and non-glacial depositional systems that were active during the LPIA. Previous authors have carried out sedimentological and stratigraphic studies in outcrops of the Itararé Group in the Santa Catarina and Paraná states, however, the integration between these areas and the delimitation of glacial cycles is still little known. Seeking to increase the knowledge on the stratigraphy of the Itararé Group, this work aims to investigate its facies in five shallow boreholes in the Mafra region, northern Santa Catarina state. In this region, 300 meters of cores sampled almost the entire stratigraphic succession of the Itararé Group. We further integrate our results with published data from Alfredo Wagner, Vidal Ramos, Presidente Getúlio, Doutor Pedrinho and São João do Triunfo in order to build a regional stratigraphic framework. A total of 33 sedimentary facies were recognized and organized in five genetic associations, corresponding to subaqueous outwash fans, rain-out and mud settling, thin-bedded turbidites, mass- transport deposits, and thick-bedded turbidites. The regional stratigraphic correlation allowed the recognition of 5 glacial cycles, corresponding to depositional sequences of deglaciation. They show signs of glacial influence that diminish toward the top, where deltaic deposits developed as climatic conditions improved. Diamictites are present in all areas and distributed preferentially in the lower and middle sequences. They consist of mass- transport deposits with origin attributed to gravitational instability due to sediment accumulation in melting and glacial retreat phases.